Lithium niobate on insulator: an emerging nanophotonic crystal for optimized light control - Midhun Murali; Amit Banerjee; Tanmoy Basu (Beilstein Journal of Nanotechnology)
Lithium niobate (LN) stands out as a versatile nonlinear optoelectronic material which can be directly applied in tunable modulators, filters, parametric amplifiers, and photonic integrated circuits. Recently, LN photonic crystals have garnered attention as a compelling candidate for incorporation into photonic integrated circuits, showcasing their potential in advancing the field. Photonic crystals possess a widely acknowledged capability to manipulate the transmission of light modes, similar to how nanostructures have been utilized to regulate electron-related phenomena. Here we study the optical performance of a one-dimensional stacked photonic crystal based on LN and TiO2/SiO2. We studied the quarter wavelength multi-layered stack using electromagnetic simulation. The forbidden-frequency region indifferent from the bulk material has been observed around 1.55 µm. A high refractive index and non-linear optical and electro-optical properties enable LN to be used for more efficient manipulation of light. The highly reflective quarternary stack can play an important role in diverse fields such as photonics, optomechanics, optoelectronics, signal processing, and quantum technologies, spanning the spectrum from photon generation (including single-photon sources and lasers) to their manipulation (encompassing waveguiding, beam splitting, filters, and spin–photon entanglement), and detection (involving single-photon detectors).